MUR1‐mediated cell‐wall fucosylation is required for freezing tolerance in Arabidopsis thaliana. Issue 4 (7th November 2019) - Panter, Paige E.; Kent, Olivia; Dale, Maeve; Smith, Sarah J.; Skipsey, Mark; Thorlby, Glenn; Cummins, Ian; Ramsay, Nathan; Begum, Rifat A.; Sanhueza, Dayan; Fry, Stephen C.; Knight, Marc R.; et al.
Summary: Forward genetic screens play a key role in the identification of genes contributing to plant stress tolerance. Using a screen for freezing sensitivity, we have identified a novel freezing tolerance gene, SENSITIVE‐TO‐FREEZING8, in Arabidopsis thaliana. We identified SFR8 using recombination‐based mapping and whole‐genome sequencing. As SFR8 was predicted to have an effect on cell wall composition, we used GC‐MS and polyacrylamide gel electrophoresis to measure cell‐wall fucose and boron (B)‐dependent dimerization of the cell‐wall pectic domain rhamnogalacturonan II (RGII) in planta . After treatments to promote borate‐bridging of RGII, we assessed freeze‐induced damage in wild‐type and sfr8 plants by measuring electrolyte leakage from freeze‐thawed leaf discs. We mapped the sfr8 mutation to MUR1, a gene encoding the fucose biosynthetic enzyme GDP‐d ‐mannose‐4, 6‐dehydratase. sfr8 cell walls exhibited low cell‐wall fucose levels and reduced RGII bridging. Freezing sensitivity of sfr8 mutants was ameliorated by B supplementation, which can restore RGII dimerization. B transport mutants with reduced RGII dimerization were also freezing‐sensitive. Our research identifies a role for the structure and composition of the plant primary cell wall in determining basal plant freezing tolerance and highlights the specific importance of fucosylation, most likely through its effect on the ability of RGII pectin to dimerize.